Differential Role of “Signal 3” Inflammatory Cytokines in Regulating CD8 T Cell Expansion and Differentiation in vivo - Pham, Nhat-Long; Badovinac, Vladimir; Harty, John (Frontiers in Immunology, 2011)
Following an infection, naïve CD8 T cells are stimulated by dendritic cells displaying pathogen-derived peptides on MHC-class I molecules (signal 1) and costimulatory molecules (signal 2). Additionally, pathogen-induced inflammatory cytokines also act directly on the responding CD8 T cells to regulate their expansion and differentiation. In particular, both type I interferons (IFNs) and IL-12 have been described as critical survival signals (signal 3) for optimal CD8 T cell accumulation during the expansion phase. Furthermore, expansion in numbers of antigen-specific CD8 T cells is coupled with their acquisition of effector functions to combat the infection. However, it still remains unclear whether these same cytokines also regulate the effector/memory differentiation program of the CD8 T cell response in vivo. Here, we demonstrate that defective signaling by either type I IFNs or IL-12 to the responding CD8 T cells impairs maximal expansion in response to DC immunization + CpG ODN, but neither of these cytokines is essential to regulate the effector/memory differentiation program. In addition, lack of direct IL-12 signaling to CD8 T cells accelerates the development of central memory phenotype in both primary and secondary antigen-specific memory CD8 T cells.